Features of Ebola Virus Disease at the Late Outbreak Stage in Sierra Leone: Clinical, Virological, Immunological, and Evolutionary Analyses. (9th May 2017) - Jiang, Tao; Jiang, Jia-Fu; Deng, Yong-Qiang; Jiang, Bao-Gui; Fan, Hang; Han, Jian-Feng; Hu, Yi; Zhuang, Dao-Min; Kargbo, David; An, Xiao-Ping; Mi, Zhi-Qiang; Zhao, Guang-Yu; et al.
Summary: We describe the clinical, immunological, and evolutionary features of Ebola virus, as well as some factors associated with low fatality rates during the late stage of the outbreak in Sierra Leone which will further understanding of the pathogenesis of Ebola virus. Abstract: We performed Ebola virus disease diagnosis and viral load estimation for Ebola cases in Sierra Leone during the late stage of the 2014–2015 outbreak (January–March 2015) and analyzed antibody and cytokine levels and the viral genome sequences. Ebola virus disease was confirmed in 86 of 1001 (9.7%) patients, with an overall case fatality rate of 46.8%. Fatal cases exhibited significantly higher levels of viral loads, cytokines, and chemokines at late stages of infection versus early stage compared with survivors. The viruses converged in a new clade within sublineage 3.2.4, which had a significantly lower case fatality rate.